Volunteering to serve: An international comparison of volunteer police officers in a UK North East Police Force and a US Florida Sheriff's Office. (September 2015) - Pepper, Ian K.; Wolf, Ross
Volunteers within the police service are an understudied but invaluable area of policing, both in the UK and the USA. Although across England and Wales there are standardised policies governing the recruitment, training and deployment of volunteer police officers, across the United States there is no national standard for their use. As a result, research comparing and contrasting across these national boundaries is of value. This current study examines similarities and differences of two policing agencies, Cleveland Police in the North East of England, and the Orange County Sheriff's Office (OCSO) in Florida, USA. Results show that while the agencies have similarities in employment status, gender and experience as a volunteer, OCSO volunteer deputies were older than their Cleveland counterparts, and were much more inclined to participate in volunteer policing because of their past experience as full-time regular police officers.